RANCANG BANGUN SISTEM PENDINGIN SEDERHANA SAYURAN DENGAN MEDIA ES - Marthin L King; Iskandar . Badil; Sudiadi . (Jurnal Turbulen, 2019)
Refrigerators are one of the alternative tools for storing vegetables so that they are not quickly damaged and rot which is currently used by many vegetable traders or housewives. Refrigeration machines certainly require electricity as a refrigerator besides not all households have refrigerators or commonly called refrigerators. Therefore it is necessary to design a simple vegetable refrigerator system with ice cube media, which does not use electricity and is very economical in addition to helping the community to store the vegetables so that they are not damaged and rot quickly. This cooling system starts from ice cubes as the main medium, which produces cold air, which is at the top of the vegetable rack and the cold steam will drop down and spread throughout the cooling room. Research conducted on how long the ice cube will melt, calculating the maximum cold temperature produced in the cooling room, looking for efficiency and comparing vegetables stored in the cool room with vegetables in the open air. Keywords: : re-bulit, refrigerator,vegetable, ice cubes